1992
DOI: 10.1128/mcb.12.8.3439
|View full text |Cite
|
Sign up to set email alerts
|

The functional importance of a cap site-proximal region of the human prointerleukin 1 beta gene is defined by viral protein trans-activation.

Abstract: Prointerleukin 11 (IL-11) is a cytokine that mediates a broad range of biological activities. Genomic sequences that regulate IL-1l transcription include both inducible regulatory elements located more than 2,700 bp upstream of the transcriptional start site (cap site) and proximal elements located near the TATA box of this gene. In this study, we focused on the identification and characterization of trans-acting nuclear regulatory proteins that bind to the cap site-proximal region of the human IL-1j gene. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
43
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 47 publications
2
43
0
Order By: Relevance
“…Unincorporated nucleotides were removed using Sephadex G-25 columns (5 Prime33 Prime, Boulder, CO). Nuclear extracts (typically 5 g) were incubated with radiolabeled probe DNA (0.1 ng, typically 10,000 cpm) in the presence of 2 g of poly(dI-dC)⅐(dI-dC) (Pharmacia, Piscataway, NJ), 1.0 mM EDTA, 10 mM Tris-HCl (pH 7.9), 25 mM glycerol, and 0.5 mM DTT as previously described (36,38). Binding reactions were incubated at room temperature for 30 min.…”
Section: Emsa Analysismentioning
confidence: 99%
“…Unincorporated nucleotides were removed using Sephadex G-25 columns (5 Prime33 Prime, Boulder, CO). Nuclear extracts (typically 5 g) were incubated with radiolabeled probe DNA (0.1 ng, typically 10,000 cpm) in the presence of 2 g of poly(dI-dC)⅐(dI-dC) (Pharmacia, Piscataway, NJ), 1.0 mM EDTA, 10 mM Tris-HCl (pH 7.9), 25 mM glycerol, and 0.5 mM DTT as previously described (36,38). Binding reactions were incubated at room temperature for 30 min.…”
Section: Emsa Analysismentioning
confidence: 99%
“…The only studies to date that have demonstrated a role for PU.1 in the regulation of the LPS response have come from work on the IL-1␤ gene and the human immunodeficiency virus-1 long terminal repeat. A cap site-proximal region of the human IL-1␤ promoter was shown to bind a factor originally termed NF␤A that was critical for the expression of IL-1␤ in response to LPS and cytomegalovirus immediate early gene products (26,27). NF␤A was later found to be identical to PU.1 (28).…”
mentioning
confidence: 99%
“…Reports of studies using the human cytomegalovirus immediate-early 1 gene product have identified proximal promoter elements, localized between -131 and + 14 bp, which appear to be involved in IL-1,B upregulation (9,21,24). In addition, an element located near the TATA box was shown to bind a specific factor termed NFIL-10A and was found to be necessary for both basal and inducible levels of IL-1i promoter activity (21 (26). U937 cells stimulated with a combination of LPS and PMA show a synergistic induction in the level of IL-lp mRNA over either treatment alone (reference 28 and unpublished observations).…”
mentioning
confidence: 99%